Development of β-Correction Spectrophotometric Principle and Analysis to Chelates Characteristics - Gao, Hong-Wen (Asian Journal of Chemistry, 2010)
A new analytical principle, named β-correction spectrophoto-metric principle, has been developed for the determination of trace amounts of metal and the analysis of its chelates' characteristic parameters. It is first to eliminate completely the interference of the excess of a ligand from its coloured solution with a metal to give out the real absorbance of the formed chelate. The reactions of gold(III) and silver(I) with p-dimethylaminobenzal rhodanine (PDR) have been used for the determination of their chelates' composition ratio (γ) and practical molar absorptivity (εP) and the determination of trace amounts of copper has been made with the calculation of the above characteristic parameters, using the new reaction of copper and the ligand, o-bromobenzenediazoaminobenzene-p-azobenzene (OBDA) at pH 12. Results showed that the chelates formed are AU2(PDR), Ag(PDR) and Cu(OBDA)2, their respective εp to 2.79 X 109, 1.31 x 104 both at 550 nm and 9.41 x 104 L mol–1 cm–1 at 500 nm. The determination for the analysis to practical samples showed that the relative standard deviations were less than 3.1 % and the recovery of copper is between 91 and 106%.